Review of the Potential use of Poly (lactic-co-glycolic acid) as Scaffolds in Bone Tissue Recovery - Saptaji, Kushendarsyah; Asriyanti, Asriyanti; Khoiriyah, Nisa; Muryanti, Laely; Setiawan, Iwan (Makara Journal of Science, 2024)
Scaffolds are used as temporary tissue in the human body to expedite healing. Biocompatible materials play a vital role in the field of tissue engineering. Therefore, they can be used to reduce human pain as soon as possible. Polymeric materials are widely used to replicate bone tissue. Poly(lactic-co-glycolic acid) (PLGA) is a potential material for bone tissue scaffolds because of its superior properties, including compatibility with the human body. Accordingly, adding hydroxyapatite and introducing different fabrication methods can enable the production of PLGA scaffolds with good abilities to help cells grow, expand, differentiate, and proliferate. The paper reviews the current development of the biocompatible material PLGA as bone tissue scaffolds. It focuses on the applications, properties, improvements, and sustainability of PLGA.